2018
DOI: 10.1101/457697
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Two Chloroflexi classes independently evolved the ability to persist on atmospheric hydrogen and carbon monoxide

Abstract: 23Bacteria within aerated environments often exist within a variety of dormant forms. In 24 these states, bacteria endure adverse environmental conditions such as organic 25 carbon starvation by decreasing metabolic expenditure and using alternative energy 26 sources. In this study, we investigated the energy sources that facilitate the 27 persistence of the environmentally widespread but understudied bacterial phylum 28 Chloroflexi. A transcriptome study revealed that Thermomicrobium roseum (class 29 Chlor… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
39
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 66 publications
7
39
0
Order By: Relevance
“…Currently, there are 188 draft genomes with more than 90% completeness deposited in the NCBI database as of May 2019 1 and 546 genomes (>50% complete and <10% contamination) are listed in the Genome Taxonomy Database (GTDB) (Parks et al, 2018). Interestingly, Chloroflexi isolates exhibit a broad diversity of phenotypes and a wide range of metabolic activities (Hug et al, 2013;Islam et al, 2019) and are often found as important members in the environment (Hanada et al, 2002;Taş et al, 2009;Chang et al, 2011;McIlroy et al, 2016;Livingstone et al, 2018). However, as the numbers show they are apparently difficult to cultivate.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there are 188 draft genomes with more than 90% completeness deposited in the NCBI database as of May 2019 1 and 546 genomes (>50% complete and <10% contamination) are listed in the Genome Taxonomy Database (GTDB) (Parks et al, 2018). Interestingly, Chloroflexi isolates exhibit a broad diversity of phenotypes and a wide range of metabolic activities (Hug et al, 2013;Islam et al, 2019) and are often found as important members in the environment (Hanada et al, 2002;Taş et al, 2009;Chang et al, 2011;McIlroy et al, 2016;Livingstone et al, 2018). However, as the numbers show they are apparently difficult to cultivate.…”
Section: Introductionmentioning
confidence: 99%
“…A characteristic bacterial group for the early stages from bare sand to lichen was candidate phylum WD272, currently known as WPS‐2 and recently named Candidatus Eremiobacterota, ‘desert bacterial phylum’, which are proposed to be autotrophs able to use atmospheric H 2 and carbon monoxide (CO) as energy sources (Ji et al , ; Holland‐Moritz et al , ). Another potential H 2 ‐ and CO‐oxidising bacterial group in the moss and lichen stages was members of Chloroflexi classified as Ktedonobacteria (King & King, ; Islam et al , ). The increased occurrence of WD272 and Chloroflexi in the moss and lichen stages suggests that they may form a basis of biomass accumulation in the Arctic sand dune succession.…”
Section: Discussionmentioning
confidence: 99%
“…The level of contamination was proportional to the volume of the vial and the mass of rubber (a proxy for the specific surface area in contact with the enclosed gas phase); therefore, form factor and volume of vials have to be considered. For example, serum vials with an increased volume of >100 mL and thus lower exposed surface area relative to volume may still be suitable for gas storage or incubation experiments lasting a few weeks, if treated stoppers are used (Islam et al, 2019(Islam et al, , 2020Kessler et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Samples were then measured 5 times over the course of 9 days; samples were measured repeatedly, except for 3 mL control Exetainers which were discarded after measurements due to insufficient volume for repeated sampling. Measurements of H 2 , CO and CH 4 were performed on a VICI TGA 6k equipped with an autosampler and a sample-injection loop of 1 mL, using a pulse-discharge helium ionisation detector as described earlier (Islam et al, 2019). The detection limits for the three gases were 61 ppb for H 2 , 10 ppb for CO and 170 ppb for CH 4 as determined by replicate samples (n=7) of zero-grade air zero (BOC Australia, North Ryde NSW, Australia).…”
Section: Demonstration Of Trace-gas Release From Rubber Materialsmentioning
confidence: 99%